Participatory Integrated Climate Services for Agriculture (PICSA) Intermediary Training, Kiteto District, Tanzania - Gathenya, John (2017)
A Participatory Integrated Climate Services for Agriculture (PICSA) training workshop for extension workers from Kiteto District of Tanzania was conducted in Arusha town from 3rd to 7th October 2016. The aim of the workshop was to equip 35 extension workers with skills to implement PICSA in their villages and wards during the October-November-December season of 2016-2017. The training consisted of short presentations by facilitators, group discussions and presentations by participants, a field practice session and a planning session. The extension workers learnt how to use local climate information from historical data to seasonal forecasts to reduce risks associate with climate variability. Each of the extension workers was expected to go back to their duty stations and train farmers how to use climate information to make better decisions in the farms. In this way, the agricultural productivity would be increased and farmers would become more resilient to future climate change.